¿LOS HUESOS SON ESTRUCTURAS GENÉTICAS, METABÓLICAS, BIOMECÁNICAS, O TODO A LA VEZ? - Cointry, Gustavo R.; Capozza, Ricardo F.; Feldman, Sara; Reina, Paola; Grappiolo, Irene; Ferretti, Sebastián E.; Mortarino, Pablo; Chiappe, María A.; Ferretti, José Luis (Actualizaciones en Osteología, 2024)
-